Evaluación técnico financiera de la obtención de biodiesel, partiendo de aceite de tilapia proveniente de la empresa Todo Pez del Huila (2019)
The present project studies the technical and financial feasibility of obtaining biodiesel, using fish oil as raw material, through the transesterification reaction. This reaction produces biodiesel and glycerin from any fat or oil and an alcohol, in the presence of a catalyst. The alcohol selected was methanol and the catalyst KOH. The experimental development of the project was carried out in the laboratories of TecnoParque. The oil, given by the company Todo Pez, was characterized to determine its initial properties and thus select the most appropriate refining route. It was decided to subject it to a chemical refining process and the material losses were close to 25%. Once the refining was completed, biodiesel was produced.